Estudio de pre factibilidad para la instalación de una planta procesadora de escamas de polipropileno reciclado - De Azambuja Hevia, Joao Alberto (2018)
This research project´s main objective is to understand the viability of installing a recycled polypropylene pellets manufacturing plant. This goes in hand with the identified issue at both a national and international level, related to the amount of garbage and waste that human beings are producing. The solution for this issue is recycling, which is the topic developed in this investigation, focused specifically on polymers. Along the document, several themes will be developed which include the market study and project demand in order to fully understand the industrial sector being approached, both the historical and potential demand, the supply, target market and commercial strategies. Then, the plant localization and optimum size are analyzed based on the critical macro and micro factors determined to guarantee the success of the project and explain the selection of the localization. Later, the project engineering is developed with the product specifications, technology and machinery to be used, installed capacity, production requirements and plant arrangement. Further on, the organization and administration is proposed and finally an economic, financial and social analysis is performed to evaluate the project and lead to solid conclusions. All of this is done to determine if the project is feasible economically, financially and socially. In the economic evaluation, a positive VAN of S/ 706 176 is obtained and a TIR of 25,04%, while in the financial evaluation the result is a positive VAN of S/ 1 003 242 and a TIR of 31,60%. In both cases, the project demonstrates that it is profitable and with a higher TIR in comparison to the market cost opportunity calculated to be 18,51%. In the social aspect, all social indicators are favorable as it is shown in the results of capital intensity (0,36) and revenue generation (0,05).